Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acscatal.8b01022
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 Reduction to CO in Water using Earth-Abundant Metal and Nitrogen-Doped Carbon Electrocatalysts

Abstract: Earth-abundant transition metal (Fe, Co, or Ni) and nitrogen-doped porous carbon electrocatalysts (M-N-C, where M denotes the metal) were synthesized from cheap precursors via silica-templated pyrolysis. The effect of the material composition and structure (i.e., porosity, nitrogen doping, metal identity, and oxygen functionalization) on the activity for the electrochemical CO2 reduction reaction (CO2RR) was investigated. The metal-free N-C exhibits a high selectivity but low activity for CO2RR. Incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(261 citation statements)
references
References 42 publications
(126 reference statements)
13
233
0
4
Order By: Relevance
“…Both the nature of the metal site and the corresponding coordination environment can affect the adsorption energies of *COOH, *CO, and CO on MN 4 , thus determining their activity and selectivity during the CO 2 RR. A combination of theory and experimental results suggests that the CO 2 RR activity of MN 4 sites follows the trend Ni ≥ Fe > Co . Recently, five MN x catalysts (M = Ni, Fe, Co Mn, and Cu) were investigated by Ju et al At low overpotentials, the first electron transfer to generate a surface adsorbed *COOH species is usually the rate‐determining step for CO evolution.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis Formentioning
confidence: 99%
“…Both the nature of the metal site and the corresponding coordination environment can affect the adsorption energies of *COOH, *CO, and CO on MN 4 , thus determining their activity and selectivity during the CO 2 RR. A combination of theory and experimental results suggests that the CO 2 RR activity of MN 4 sites follows the trend Ni ≥ Fe > Co . Recently, five MN x catalysts (M = Ni, Fe, Co Mn, and Cu) were investigated by Ju et al At low overpotentials, the first electron transfer to generate a surface adsorbed *COOH species is usually the rate‐determining step for CO evolution.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis Formentioning
confidence: 99%
“…Recently, carbon-based solid catalyst materials doped with nitrogen and nitrogen-coordinated transition metals (MÀ NÀ C) have emerged as a selective and cost-efficient alternative to noble metal catalysts for the direct electrochemical reduction of CO 2 to CO. [13][14][15][16][17][18] Such materials have been widely studied as an alternative to Pt catalyst for the Oxygen Reduction Reaction (ORR) in cathode's fuel cells. [19][20][21][22] To explore the possibility of using MÀ NÀ C catalyst for the CO2RR Tripkovik et al, performed Density Functional Theory calculations (DFT) on porphyrin-like metal-functionalized graphene structures and found that these materials should in fact be active in the reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure B–D shows the performance of several M‐N‐C electrocatalysts for the CO 2 RR in CO, along with their faradaic efficiencies for CO generation and the ideal overpotentials to achieve syngas formation (Figure B). Fe‐N‐C electrocatalysts exhibit the highest CO formation activity and selectivity at low overpotentials ( E =−0.3 to −0.5 V vs. RHE), similar to N‐C, although N‐C catalysts exhibit a lower overall current, whereas Ni‐N‐C electrocatalysts dominate regarding selectivity/activity at higher overpotentials. Because of their more thermodynamically favorable nature toward the HER, Co‐N‐C electrocatalysts, driven by the activity of their CoN 4 sites, exhibit a lower selectivity for CO production throughout the entire potential range.…”
Section: M‐n‐c Electrocatalysts For Syngas Generation: a Selectivitymentioning
confidence: 98%
“…For example, most CO 2 RR characterizations are carried out in KHCO 3 solution (phosphate‐buffered), as CO 2 replenishment at the electrocatalyst interface is easier; this results in enhanced faradaic efficiency for CO 2 RR with respect to HER . Also, Hu et al . observed FE CO =50–90 % for Fe‐N‐C electrocatalysts in 0.5 m KHCO 3 , and Wu et al .…”
Section: M‐n‐c Electrocatalysts For Syngas Generation: a Selectivitymentioning
confidence: 99%